2015
DOI: 10.1002/pola.27545
|View full text |Cite
|
Sign up to set email alerts
|

Polyisobutylene-b -Poly(N,N -diethylacrylamide) well-defined amphiphilic diblock copolymer: Synthesis and thermo-responsive phase behavior

Abstract: Polyisobutylene-b-poly(N,N-diethylacrylamide) (PIBb-PDEAAm) well-defined amphiphilic diblock copolymers were synthesized by sequential living carbocationic polymerization and reversible addition-fragmentation chain transfer (RAFT) polymerization. The hydrophobic polyisobutylene segment was first built by living carbocationic polymerization of isobutylene at 270 C followed by multistep transformations to give a welldefined (M w /M n 5 1.22) macromolecular chain transfer agent, PIB-CTA. The hydrophilic poly(N,N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A variety of prior studies have used radical chemistry or other routes to prepare diblock copolymers from polyisobutylene or other polyolefins . These studies have shown that click chemistry followed by other reactions is one route to diblock PIB derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of prior studies have used radical chemistry or other routes to prepare diblock copolymers from polyisobutylene or other polyolefins . These studies have shown that click chemistry followed by other reactions is one route to diblock PIB derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is conceptually simpler it can be synthetically challenging as stringent reaction conditions are required and only monomers polymerisable via LCP are viable, such as styrene 13 and vinyl ethers. 14 Alternatively, the site transformation also utilises end groups present on PIB but is much more versatile as end group can be modied to a range of polymerisation initiators or mediators compatible with many polymerisations techniques; such as living anionic polymerisation, 15 group transfer polymerisation, 16 reversible addition fragmentation chain transfer (RAFT) polymerisation, 17,18 atom transfer radical polymerisation (ATRP) [19][20][21] and using the same initiators it may be possible to utilise single electron transfer living radical polymerisation (SET-LRP). This allows the polymerisation of other monomer classes like (meth)acrylates and (meth)acrylamides.…”
Section: Introductionmentioning
confidence: 99%